The influence of the attributes of "Internet of Things" products on functional and emotional experiences of purchase intention - Luis Hernan Contreras Pinochet; Evandro Luiz Lopes; Caio Henrique Fernandes Srulzon; Luciana Massaro Onusic (Innovation & Management Review, 2018)
Purpose: "Internet of things" is a broad term used to describe network connectivity to physical objects. Called connectable or smart objects, they are embedded in electronic circuits and software that make them capable of detecting, collecting and transmitting data and information. This paper aims to examine the influence of the attributes of "internet of things" products in the functional and emotional experience of purchase intention. Design/methodology/approach: The study used a model adapted from Yaping et al. (2014), with adjustment for the constructs "emotional experience", "functional experience" and "purchase intention". The survey consisted of a sample of 747 valid questionnaires regarding users of "internet of things" products, through a structured questionnaire with 36 assertions, which were answered based on the Likert scale. The quantitative research approach followed an exploratory descriptive phase followed by the application of structural equation modeling. Findings: Results validated most of the relationships of the model, with high levels of significance. In addition, there was a greater influence of emotional experience than functional on purchase intention for the selected sample, which mainly consisted of young people. Originality/value: In short, the study confirmed the statistical significance of the structural paths, indicating that the proposed model is consistent, and with an appropriate adjustment can be applied in future research.
Keywords: 650; Internet of things; Purchase intention; Structural equation modeling